2010
DOI: 10.1117/12.853853
|View full text |Cite
|
Sign up to set email alerts
|

Feature extraction of the wear label of carpets by using a novel 3D scanner

Abstract: In this paper we present a novel 3D scanner to capture the texture characteristics of worn carpets into images of the depth. We first compare our proposed scanner to a Metris scanner previously attempted for this application. Then, we scan the surface of samples from the standard EN1471 using our proposed scanner. We found that our proposed scanner offers additional benefits because it has been specifically designed for carpets, performing faster, cheaper, better and also a lot more suitable for darker carpets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…These photographs were converted from the RGB-model to the YUV-model, with values from 1 to 256, to use an intensity component more shape representative. To compose the database of range images, the samples were also scanned with the 3D scanner we proposed in Orjuela et al, 13 in which the depth information of the surface of a carpet is digitize. To scan, the carpet is placed on a drum and on its surface a uniform line is project.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These photographs were converted from the RGB-model to the YUV-model, with values from 1 to 256, to use an intensity component more shape representative. To compose the database of range images, the samples were also scanned with the 3D scanner we proposed in Orjuela et al, 13 in which the depth information of the surface of a carpet is digitize. To scan, the carpet is placed on a drum and on its surface a uniform line is project.…”
Section: Methodsmentioning
confidence: 99%
“…12,13,15 Particularly, using an extension of the known rotational Local Binary Pattern (LBPROT) 17 technique named LBPRMC (from Local Binary Pattern Rotational, Mirrored and Complemented invariant) has shown that grouping patterns increases the linear rank of the features related to the degree of wear as well as the discrimination between consecutive degrees of wear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The range images were composed by scanning the carpet samples with the scanner based on structured light described in Orjuela et al [12]. The surface reconstruction of the range image was based on a wavelet edge detector [17].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have proposed an automatic assessment system based on extracting texture parameters from intensity color and depth (range) images [11]. The range images are obtained using our own scanner specifically designed for carpets [12]. We have composed our own carpet database following the European standard [3,4].…”
Section: Introductionmentioning
confidence: 99%